Anxiety and prosocial behavior in adolescents of a school in Los Olivos–Peru in the context of COVID-19 - Samochuallpa-Solis, Sonia (2024)
Objective: To evaluate the relationship between anxiety and prosocial behavior in students from a High School (HS) in the district Los Olivos – Lima, in the context of the COVID-19 pandemic. Methods: A cross-sectional descriptive correlational design study. 137 students from first to fifth year of HS, between the ages of 12 and 17 years were evaluated. The State-Trait Anxiety Inventory (STAI) and the Prosocial Behavior Scale in Adolescents were applied. Results: The most frequent level of state anxiety (S/A) was “moderate”, found mainly among second year high school students (80.65%), while for trait anxiety (T/A), it was “high”, particularly detected in fourth HS students (70.96%). In relation to prosocial behavior, the most frequent was the “moderate” level, standing out in fourth year students (64.53%). Likewise, positive (although very low) correlations were found between prosocial behavior and T/A with a Pearson r of 0.188 (p = 0.028), and between prosocial behavior and S/A with a Pearson r of 0.180 (p = 0.036). Conclusions: There is a statistically significant positive relationship between T/A and S/A and prosocial behavior in adolescent students from a private diocesan HS in a district of Northern Lima.